Global economic costs and knowledge gaps of invasive gastropods - Xiaoming Jiang; Peng Zheng; Ismael Soto; Phillip J. Haubrock; Jing Chen; Lei Ji (Ecological Indicators, 2022)
Invasive alien gastropods are a particularly pervasive taxonomic group worldwide, often causing substantial impacts on aquatic and terrestrial ecosystems. Yet, much remains unknown about this invasive group’s economic costs to human society. Here, we used the InvaCost database to evaluate the taxonomic, spatial, and temporal patterns of economic costs associated with invasive gastropods on the global scale. In total, 13 species of invasive gastropods caused a cumulative global cost of US$ 3.94 billion over the period 1966–2020, with a majority being attributed to aquatic species ($ 3.72 billion, 94.4 %, concentrated mostly in Asia) and only $ 0.22 billion (5.6 %, concentrated mostly in Europe) to terrestrial species. Among different regions, Asia (3.71 billion) reported the greatest costs, compared to far lower costs reported in Europe (214.50 million), North America (13.80 million), Oceania (2.69 million), South America (<1 million) and Africa (<1 million). The vast majority (94.2 %) of these costs were due to the family Ampullariidae and the genus Pomacea (apple snails) which were largely reported in Asia. Furthermore, 88.4 % of total gastropod-related costs resulted from direct resource damages and losses, being one order of magnitude higher than management related costs (9.0 %). A majority (81.5 %) of total gastropod costs was incurred by agriculture, and relatively little was attributed to authorities and stakeholders (6.3 %), public and social welfare (4.8 %) and mixed (7.3 %) impacted sectors. Average annual costs amounted to $ 71.63 million, most of which ($ 67.64 million) occurred in aquatic environments. Despite the increasing economic losses caused by invasive gastropods, we identified significant knowledge gaps in cost information of many well-known invasive gastropods. Thus, we appeal for further urgently needed research efforts to quantify costs of invasive gastropods to fill the knowledge gaps, in order to better evaluate this group’s true magnitude of monetary costs.